The spatial and molecular ecology of Twite linaria flavirostris - Dunning, Jamie (2019)
Twite Linaria flavirostris have a globally disjunct population, with breeding groups in western Europe and from central to east Asia, yet the phylogeographic consequences of this distribution have remained largely uninvestigated. Furthermore, recent population declines in Western Europe now underpin the need to better understand within-species population limits and migratory ecology. This study sought to investigate connectivity and population structure at differing scales within the Twite’s global distribution. Data was accessed from ringing schemes across Europe to infer spatio-temporal trends within the Western European breeding group. Mixing between the endemic British subspecies L. f. pipilans and the Scandinavian L. f. flavirostris is rare and may be perpetuated by differing migratory ecologies. Weak connectivity within the continental group is considered to be a response to instability in available food during the non- breeding season; the findings also suggests a lack of migratory plasticity within the British group. Two regions of the mitochondrial DNA, cyt-b and COI were sequenced in order to explore population structure across the global distribution. A number of informative sites in the mitochondrial DNA identified three narrowly divergent and relatively invariable haplogroups, a single western European, a closely related central Asian group and a divergent Himalayan group. These data are suggestive of recent population expansion within the closely related European and Central Asian groups and, probably related to Pleistocene glacial cycles. Museum specimens were accessed in an attempt to fill gaps in sampling, however sequences retrieved likely contained contaminating DNA. Over all, this study finds isolation within Western Europe and suggests a revision to current IUCN classifications within the region. Future works should seek more comprehensive sampling within the Asian group in order to better understand population limits and connectivity.